2012
DOI: 10.1590/s0100-879x2012007500033
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed ultrasound therapy accelerates the recovery of skeletal muscle damage induced by Bothrops jararacussu venom

Abstract: We studied the effect of pulsed ultrasound therapy (UST) and antibothropic polyvalent antivenom (PAV) on the regeneration of mouse extensor digitorum longus muscle following damage by Bothrops jararacussu venom. Animals (Swiss male and female mice weighing 25.0 ± 5.0 g; 5 animals per group) received a perimuscular injection of venom (1 mg/kg) and treatment with UST was started 1 h later (1 min/day, 3 MHz, 0.3 W/cm2, pulsed mode). Three and 28 days after injection, muscles were dissected and processed for light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Recent accumulating studies have reported that the mechanical modalities, such as ultrasound (US) and electrical stimulation have therapeutic effects in various diseases [7][8][9][10]. In particular, US at the frequency of 3 to 10 MHz has been used in general in clinical applications, mainly for diagnostic and therapeutic purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent accumulating studies have reported that the mechanical modalities, such as ultrasound (US) and electrical stimulation have therapeutic effects in various diseases [7][8][9][10]. In particular, US at the frequency of 3 to 10 MHz has been used in general in clinical applications, mainly for diagnostic and therapeutic purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Bothrops jararacussu ( Figure 1A) is widely distributed in Southeast region of Brazil (B ernils & Costa, 2015;Uetz & Ho sek, 2015); adult specimens can achieve 2.2 m length and accidents can cause local necrosis, shock, systemic bleeding and acute kidney injury (Milani et al, 1997). In vitro studies show that the venom of B. jararacussu causes irreversible neuromuscular blockade and muscle contracture, thus evidencing venom neurotoxic activity; histology of the muscle shows that muscle fibres exhibit pathologic states indicating that venom possesses myotoxic activity too (Ferraz et al, 2014;Oshima-Franco et al, 2000;Paiva-Oliveira et al, 2012;Patrão-Neto et al, 2013;Saturnino-Oliveira et al, 2012). The Lys49-PLA 2 BthTX-I, its major toxin, is able to reproduce the neuromuscular irreversible blockade, muscle contracture and membrane depolarization induced by crude venom in in vitro nervemuscle preparations; likewise the toxin is highly myotoxic (Cavalcante, Silva, & Gallacci, 2005;Ferraz et al, 2014;Oshima-Franco et al, 2001, 2004.…”
Section: Introductionmentioning
confidence: 99%
“…The myotoxicity of crovirin was studied ex vivo using a muscle creatin kinase (CK) activity assay [55] . The analysis consisted of monitoring the rate of CK release from isolated mouse extensor digitorum longus (EDL) muscle bathed in a solution containing crovirin (10 µg/ml).…”
Section: Methodsmentioning
confidence: 99%